Functional outcome of intracapsular neck of femur fracture treated in elderly with bipolar hemiarthroplasty at tertiary health care center - Madavi, Ashwinikumar Arvind; Agrawal, Mukesh; Ravariya, Rahul Vithal; Konde, Shivraj; Doshi, Suraj (International Journal of Research in Orthopaedics, 2025)
Background: Fractures of the neck of the femur are common in the elderly and are expected to rise significantly due to increased life expectancy. While conservative management has limited indications, surgical intervention remains the standard of care. Among surgical options, open reduction and internal fixation have shown high failure rates due to nonunion and avascular necrosis, leading to revision surgeries and increased morbidity. Aim of study was to evaluate the functional outcomes of intracapsular neck of femur fractures in elderly patients treated with cemented bipolar hemiarthroplasty. Methods: This prospective observational study was conducted at a tertiary care hospital and included 60 patients aged 60 years and above with intracapsular femoral neck fractures. All patients underwent cemented bipolar hemiarthroplasty. Functional and clinical outcomes were assessed using the Harris hip score (HHS) during follow-up visits. Patient consent and comprehensive clinical evaluations were obtained on admission. Results: The mean patient age was 69.88 years, with 55% females. According to Garden’s classification, 11.7% had grade I/II, 53.3% grade III, and 35% grade IV fractures. At 3 months post-surgery, 45% had poor, 43.3% fair, and 11.7% good functional outcomes. Conclusions: Cemented bipolar hemiarthroplasty for intracapsular femoral neck fractures in the elderly offers favorable functional outcomes, reduces complications associated with prolonged immobilization, and facilitates early rehabilitation and return to activity.